Study on Depression as a Civilization-deformed Adaptation and Defence Mechanism - Bohdan Wasilewski; Olha Yourtsenyuk; Eugene Egan (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Depression is currently one of the main barriers to further civilizational development. Despite intensive efforts, it is a growing health, social and economic problem. We still lack clarity regarding the ethology of depression and treatment is still mainly symptomatic. The authors postulate that depression has similarities with anxiety and from an evolutionary perspective is an archaic defence mechanism. Formerly, through the agency of complex psychological, biological and social mechanisms, healing was facilitated in conditions of an intense, short-term nature. Adverse civilizational and environmental changes have caused pathological changes in both the mechanism of depression and corresponding defence mechanisms such as the induction of an anxiety state. Related to depression is the mechanism of thanatosis, concerning chronic biological and psychosocial dysfunctions. It is a mechanism for activating self-eliminating processes to free the community from the burden of a dysfunctional individual. The authors of this publication continue to analyse the arguments that provide the basis for understanding depression as a civilization deformed mechanism of adaptation and defence [1].